2022
DOI: 10.5194/egusphere-egu22-10663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Strong isoprene emission response to temperature in tundra vegetation

Abstract: <p>Biogenic emissions of volatile organic compounds (BVOCs) are a crucial component of biosphere-atmosphere interactions. In northern latitudes, climate change is amplified by feedback processes in which BVOCs have a recognized, yet poorly quantified role, mainly due to a lack of measurements and concomitant modelling gaps. Hence, current Earth system models mostly rely on temperature responses measured on vegetation from lower latitudes, rendering their predictions highly uncertain.</p&am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…The posterior 𝜸 T is more than 5 times more sensitive to temperature ( Q 10 = 9.29) than the a priori ( Q 10 = 1.74). This heightened temperature sensitivity is consistent with previous studies, which have found that the a priori MEGAN 𝜸 T parameterization underestimates emissions at high temperatures for Australian eucalypt species (Emmerson et al., 2020) and Arctic vegetation (Angot et al., 2020; Kramshøj et al., 2016; Seco et al., 2020, 2022). Figure 7b shows that the median posterior 𝜸 T is also consistent with the observed γT ${\boldsymbol{\gamma }}_{\boldsymbol{T}}^{\prime }$ as calculated with daily top‐down GlobEmission fluxes, indicating that the top‐down and eddy covariance constraints are consistent with respect to the temperature dependence of emissions.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The posterior 𝜸 T is more than 5 times more sensitive to temperature ( Q 10 = 9.29) than the a priori ( Q 10 = 1.74). This heightened temperature sensitivity is consistent with previous studies, which have found that the a priori MEGAN 𝜸 T parameterization underestimates emissions at high temperatures for Australian eucalypt species (Emmerson et al., 2020) and Arctic vegetation (Angot et al., 2020; Kramshøj et al., 2016; Seco et al., 2020, 2022). Figure 7b shows that the median posterior 𝜸 T is also consistent with the observed γT ${\boldsymbol{\gamma }}_{\boldsymbol{T}}^{\prime }$ as calculated with daily top‐down GlobEmission fluxes, indicating that the top‐down and eddy covariance constraints are consistent with respect to the temperature dependence of emissions.…”
Section: Resultssupporting
confidence: 91%
“…Isoprene emissions can be estimated from tower‐ or aircraft‐based eddy covariance measurements (Guenther & Hills., 1998; Karl et al., 2009). This approach is useful for constraining the diurnal variability of isoprene emissions, making it well‐suited for characterizing the temperature response (Misztal et al., 2014; Seco et al., 2015, 2022; Yu et al., 2017). In this study, we use tower‐based eddy covariance isoprene flux measurements from the AmeriFlux site BR‐Sa1 in Brazil's Tapajós National Forest (2.86°S, 54.96°W) (Sarkar et al., 2020, 2022), as well as isoprene mixing ratio measurements from the 2018 Wytham Isoprene iDirac Oak Tree Measurements (WIsDOM) campaign in Wytham Woods near Oxford, UK (51.46°N, 1.20°W) (Ferracci, Bolas, et al., 2020, Ferracci, Harris, et al., 2020).…”
Section: Methods and Datamentioning
confidence: 99%
See 2 more Smart Citations
“…These relationships provide the basic framework of isoprene emission models that are capable of coupling with meteorology and the land biosphere, with the most widely used being the Model of Emissions of Gases and Aerosols from Nature (MEGAN) (Guenther et al, 1993(Guenther et al, , 2006(Guenther et al, , 2012(Guenther et al, , 2017. Recent work has shown stressed conditions -such as drought, heat waves, and high winds -can induce large changes in isoprene emissions, in contrast with model predictions in the absence of those stress factors (Potosnak et al, 2014;Huang et al, 2015;Kravitz et al, 2016;Seco et al, 2015;Otu-Larbi et al, 2020;Seco et al, 2022). As stressed conditions are rarely sampled by field campaigns due to their infrequent and irregular nature, they are poorly constrained; hence, stress impacts on isoprene emissions are among the least understood aspects in our predictive ability with respect to BVOC-chemistry-climate interactions.…”
Section: Introductionmentioning
confidence: 99%